2021
DOI: 10.3390/brainsci11081093
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Optical Monitoring of Cerebral Blood Flow and EEG Spectral Responses after Severe Traumatic Brain Injury: A Case Report

Abstract: Survivors of severe brain injury may require care in a neurointensive care unit (neuro-ICU), where the brain is vulnerable to secondary brain injury. Thus, there is a need for noninvasive, bedside, continuous cerebral blood flow monitoring approaches in the neuro-ICU. Our goal is to address this need through combined measurements of EEG and functional optical spectroscopy (EEG-Optical) instrumentation and analysis to provide a complementary fusion of data about brain activity and function. We utilized the diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Short-wave infrared (SWIR) wavelengths such as1064 nm has a low effective attenuation in brain tissue [44], [47], [53], [54], which (4) increases the tissue probing depth, and allows for a higher maximum permissible laser power (ANSI Z136.1 [61]) to (5) increase the SNR. Very recently we demonstrated the clinical feasibility of using a new generation photon counting detector, superconducting nanowire single photon detector (SNSPD) for CW-DCS with improved SNR at 785 nm [62]. In this paper, we show the clinical feasibility of a TG-DCS by using SNSPD, which enabled u use of a SWIR wavelength at 1064 nm in a patient with severe TBI in an ICU setting.…”
Section: Introductionmentioning
confidence: 92%
“…Short-wave infrared (SWIR) wavelengths such as1064 nm has a low effective attenuation in brain tissue [44], [47], [53], [54], which (4) increases the tissue probing depth, and allows for a higher maximum permissible laser power (ANSI Z136.1 [61]) to (5) increase the SNR. Very recently we demonstrated the clinical feasibility of using a new generation photon counting detector, superconducting nanowire single photon detector (SNSPD) for CW-DCS with improved SNR at 785 nm [62]. In this paper, we show the clinical feasibility of a TG-DCS by using SNSPD, which enabled u use of a SWIR wavelength at 1064 nm in a patient with severe TBI in an ICU setting.…”
Section: Introductionmentioning
confidence: 92%
“…Our DCS system was evaluated by comparing its output to a lab-standard reference DCS system widely used by the DCS community, which consists of a 4-channel hardware correlator (Flex01LQ-05, Correlator.com, Bridgewater, NJ) and a computer to perform software curve fitting to determine the BFI in post-processing as we have described in detail previously [20,[54][55][56]. A BNC splitter was used to feed the APD output signal to both the reference system and our FPGA DCS device so that both systems received the same photon pulses with identical optical setups.…”
Section: System Evaluation and Comparisonmentioning
confidence: 99%
“…It has previously been shown that DCS measurements correlate well with established modalities such as arterial-spin labelled magnetic resonance imaging (ASL-MRI) [7][8][9][10] and Doppler ultrasound [3,[11][12][13][14][15][16], with its advantages that DCS has a lower cost and more portability than MRI and more sensitivity to microvasculature than Doppler ultrasound. Thus, DCS has found numerous applications related to bedside monitoring of several disease conditions including acute brain injuries [1, [17][18][19][20][21][22][23][24][25][26][27][28] and monitoring of cancer therapies[1-6,29 -38].…”
Section: Introductionmentioning
confidence: 99%